HERMENEUTIKA GADAMERIAN UNTUK MEMAHAMI KUALITAS AUDIT (PEMERIKSAAN KEUANGAN) BPK RI - Ginrey Shandy Algam (Universitas Negeri Malang, 2018)
This research aim is to get an understanding of the financial audit quality of BPK RI by interpretative paradigm approach and Gadamer’s Hermeneutics as technical data analysis (text). The data (text) has shown that BPK RI still has low financial audit quality whereas people of Indonesia (as stakeholders) have expectation for high financial audit quality. Conversely, BPK RI has claimed for having high financial audit quality. Financial audit quality of BPK RI measured based on compliance of audit practice with the code of ethics and auditing standards. The results showed that the financial audit quality of the BPK RI is not in accordance with the claims, which can be observed from non-compliance with the code of ethics and auditing standards.Keywords:Audit quality, The Audit Board of The Republic Indonesia, Gadamer's Hermeneutics